Pengaruh Work Life Balance, Motivasi Dan Disiplin Kerja Terhadap Kinerja Driver Shopeefood Di Kota Malang (Studi Kasus Pada Driver Shopeefood Di Kota Malang) - Mahendra, Mochamad Jaya; Asiyah, Siti; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ This inquiry delves into how equilibrium between professional and personal life, inner drive, and adherence to work rules influence the effectiveness of ShopeeFood couriers in Malang. The subjects of this study are those couriers, with a selected group of 95 participants, chosen through a targeted sampling strategy. Data was gathered through a Google Form-based survey, and the analytical process was conducted using IBM SPSS. The findings reveal that, in combination, balance between work and life, motivation, and work discipline notably impact job performance. However, the individual effect of work-life balance and work discipline on performance appears negligible, whereas motivation stands out as a pivotal factor enhancing performance.Â Keywords: Work Life Balance, Motivasi, Disiplin Kerja, Kinerja. Shopeefood